2014
DOI: 10.1111/anae.12597
|View full text |Cite
|
Sign up to set email alerts
|

Induction of general anaesthesia by effect‐site target‐controlled infusion of propofol: influence of pharmacokinetic model and ke0 value

Abstract: SummaryWe studied the use of a new k e0 value (0.6 min À1) for the Marsh pharmacokinetic model for propofol. Speed of induction and side-effects produced were compared with three other target-controlled infusion systems. Eighty patients of ASA physical status 1-2 were studied in four groups in a prospective, randomised study. 132 (90-246 [57-435])). The Schnider model in effect-site control produced induction times that were longer (298 (282-398 [58-513])s) than those observed with the Marsh model in blood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
(36 reference statements)
0
16
0
1
Order By: Relevance
“…k e0 is the single mathematical factor needed to describe the hysteresis or delay between the timecourse of the estimated plasma-concentration and the observed effect of interest. Thomson et al [11] searched for the 'optimal' k e0 to extend the Marsh model with an effect-site compartment for electroencephalographic effects and he found that a value of 0.6/min was most accurate. However, Seo and coworkers [12] studied various extended Marsh models using various k e0 values and found different effect-site concentrations at loss and return of consciousness, dependent on the applied model.…”
Section: Pharmacokinetic-dynamic Modelsmentioning
confidence: 99%
“…k e0 is the single mathematical factor needed to describe the hysteresis or delay between the timecourse of the estimated plasma-concentration and the observed effect of interest. Thomson et al [11] searched for the 'optimal' k e0 to extend the Marsh model with an effect-site compartment for electroencephalographic effects and he found that a value of 0.6/min was most accurate. However, Seo and coworkers [12] studied various extended Marsh models using various k e0 values and found different effect-site concentrations at loss and return of consciousness, dependent on the applied model.…”
Section: Pharmacokinetic-dynamic Modelsmentioning
confidence: 99%
“…Propofol as a part of total intravenous anesthesia is applied in target‐controlled infusions, which became available in the late 1990s . Hereby the aim is to establish intended concentrations at the target organ, the brain, rather than in blood plasma . The resulting levels are initially predicted either by the pharmacokinetic/pharmacodynamic model of Schnider or by the model of Marsh, which was proven to mirror more precisely the characteristic parameters sedation score and bispectral index .…”
Section: Introductionmentioning
confidence: 99%
“…Propofol (2,6-diisopropyl-phenol) is a commonly used intravenous anesthetic agent for inducing and maintaining general anesthesia and/or sedation in intensive care. It provides a quick effect (already after 30 s) and rapid recovery of the concentrations at the target organ, the brain, rather than in blood plasma [6]. The resulting levels are initially predicted either by the pharmacokinetic/pharmacodynamic model of Schnider or by the model of Marsh, which was proven to mirror more precisely the characteristic parameters sedation score and bispectral index [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Marsh pharmacokinetic parameters (10) that are incorporated into the Diprifusor TCI system were derived from a relatively small number of healthy individuals without organs dysfunction (11). These parameters have been proven to provide a stable blood-therapeutic agent concentration for propofol induction and maintenance of anesthesia in patients without organ dysfunction (10,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%